Beyond accreditation: unraveling the narrative of public health through a critical race praxis lens - Collins, Sarah L.; Allen-Mitchell, Acquel; Smith, Travis C.; Hack, George; Stetten, Nichole E.; Moorhouse, Michael D. (Frontiers in Public Health, 2024)
Recognizing and addressing health inequities among minority populations are pivotal to public health. Further, public health strives to understand the complexities between race and health without limiting discussions around race as a trivial variable. This commitment towards equity demonstrates considerable similarities to Critical Race Theory (CRT) which led to the creation of the Public Health Critical Race (PHCR) Praxis to instill CRT within public health. However, the literature on how public health education incorporates critical race studies remains limited. The goal of this study was to examine how public health curriculum currently aligns with the PHCR praxis and meets public health's goal of health equity.: This qualitative study employed document analysis to evaluate academic syllabi from CEPH-accredited MPH programs. Stratified random sampling was applied across two sampling pools, Schools of Public Health (SPH) and Public Health Programs (PHP). Course overviews, course objectives, course curricular information, and course policies were identified and extracted from each syllabus for analysis. A total of 53 syllabi were obtained from a final sample of nine public universities and one private. Results: Through inductive and directed content analysis, a priori themes of Structural Determinism, Voice, Critical Approaches, Ordinariness of Racism, Social Construction of Knowledge, Intersectionality, Disciplinary Self-Critique, Primacy of Racialization, Race as a Social Construct, Race Consciousness, and their respective categories arose as salient. Two new themes, Antiracism Practices and Culture of Inclusivity, were also present.Discussion: This study is the first to explore public health education's current curricular practices concerning CRT and antiracist praxes. The results confirm the interwoven nature of public health education with critical race studies, as all principles of PHCR praxis were present.However, the prevalence of these principles varied, suggesting gaps in the alignment of public health curricula and CRT. It is essential that public health educators ensure that the foundational competencies students are expected to display align with public health's goal of health equity. This work can equip MPH programs and public health educators with the ability to revise or bolster their current curricular and instructional efforts to support the pursuit of health, racial equity, and social justice.